PENETAPAN PRIORITAS STRATEGI MARKETING MIX PRODUK OLAHAN KUNYIT (STUDI KASUS : UMKM RETNO WANGI) - Yos Wahyu Harinta; Yoesti Silvana Arianti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
This study aims to determine the marketing mix (4P), marketing inhibiting factors, also effective and efficient marketing strategies for processed products from Retno Wangi's turmeric MSMEs. Data collection techniques are interviews, observation and documentation. This type of research is descriptive analytical. The results showed that the four marketing mix variables had an effect on the marketing of processed turmeric products produced by Retno Wangi. In addition, the identification of the marketing mix can show the factors that hinder the marketing of processed turmeric as much as six factors from internal and four factors from external. The priority of the chosen strategy is to streamline promotions through social media (online) in order to increase marketing reach, cooperate with local governments to take care of halal stamps, BPOM permits to ensure product quality, and add resellers so that products are easier to find. anywhere. Keywords: SMEs, Retno Wangi, Turmeric, Marketing Mix